Technology, Recent Advancement, and Application of Multiple Emulsions: An Overview (Asian Journal of Pharmaceutics (AJP), 2021)
Multiple emulsions are complex polydispersed organizations where both oil-in-water and water-in-oil emulsionare present simultaneously, which are stabilized by lipophilic and hydrophilic surfactants, respectively. To achievestable multiple emulsions, the proportion of these surfactants is critical. Between the two types of multipleemulsions, water-in-oil-in-water (W/O/W) and oil-in-water-in-oil, the former has a wider range of applications andis thus investigated in more depth. Multiple emulsion development, preparation procedures, and in vitro evaluationmethodologies have all been updated. Numerous elements impacting the stability of multiple emulsions, as well asstabilization strategies, are explored in detail, with a focus on W/O/W type multiple emulsions. Multiple emulsionsare a possible carrier because they have desirable drug release mechanisms and rates, as well as a favorablein vivo fate. It has a wide range of uses, including regulated, targeted distribution, flavor masking, bioavailabilityaugmentation, enzyme immobilization, and so on. In the microencapsulation process, several emulsions have alsobeen regarded an intermediate phase. They are the systems of increasing interest for the oral delivery of hydrophilicdrugs, which are unbalanced in the gastrointestinal tract such as proteins and peptides. It will provide a novel carriersystem for the administration of pharmaceuticals, cosmetics, and medicinal agents as procedures for preparation,stabilization, and rheological characterization of multiple emulsions advance. Formulation, stabilization procedures,and prospective uses of various emulsion systems are all considered in this assessment.